Formation of a Dimer of Trinuclear Helicates which Encapsulates an Array of Six Hydrogen‐Bonded Anions. Issue 49 (16th October 2014) - Faulkner, Robert A.; Harding, Lindsay P.; Higginson, Joshua; Rice, Craig R.; Slater, Christopher
Abstract The amine‐containing ligand L, composed of two bidentate pyridyl‐thiazole moieties linked by a 1, 3‐diaminophenylene unit, reacts with copper(II) ions to form a dinuclear double helicate [Cu2L2]4+. Reaction of [Cu2L2]4+ with dihydrogen phosphate (0.5 equivalents) gives the unsaturated dinuclear double helicate [Cu2L2(OPO3H2)]3+. [Cu2L2(OPO3H2)]3+ further reacts with another 0.5 equivalents of dihydrogen phosphate to give a trinuclear circular helicate which then self‐assembles into a hexameric cluster [{Cu3L3(OPO3H2)3}]26+.